Regional and whole-brain neurofunctional alterations during pain empathic processing of physical but not affective pain in migraine patients - Dan Liu; Menghan Li; Heng Jiang; Yiqi Mi; Xiaolei Xu; Yali Zhou; Yaxian Hou; Yuquan Shen; Michael Maes; Xiao Xiao; Feng Zhou; Luca Giani; et al. (The Journal of Headache and Pain)
Abstract Background Accumulating evidence suggests that migraine patients present abnormal brain responses to salient sensory and emotional stimuli. However, it is still unclear whether this is a generalized or domain-specific phenomenon. Employing a well-validated fMRI paradigm, we investigated pain empathic reactivity across two domains: observation of physical pain (noxious stimulation) and affective pain (facial expressions). On the basis of a generalized hyperexcitability/hyperreactivity in migraine, we hypothesized abnormal responses to both dimensions of pain empathy. Methods We collected fMRI and psychometric data from 21 migraine patients and matched controls. Univariate and multivariate neuroimaging analyses were utilized to examine domain-specific dysregulations in (a) neural reactivity in meta-analytically defined shared regions of pain-empathy processing, and (b) whole-brain neurofunctional signatures of physical and affective pain empathy (VPS, Zhou et al., 2020). Logistic regression models and machine learning-based classification were employed to determine differences between groups (migraine or control). Results Migraine patients exhibit increased neural responses during empathy for physical pain in the bilateral inferior frontal gyrus (slightly more pronounced on the right side), with alterations on the right significantly associated with the pain experienced during the attack. On the whole-brain level, the predictive accuracy of the VPS for physical pain empathy was shown to be significantly higher for patients as compared to controls, reaching 100% accuracy. Across analyses, we did not find evidence of altered empathy processing for affective pain. Conclusions Contrary to our hypothesis, our results indicate that migraine patients present a domain-specific increased brain responsivity, localized in the bilateral inferior frontal gyrus but also extending to subtle whole brain patterns, during empathy for physical pain stimuli, but not during empathy for affective pain. Based on the evidence that the neural pathways for empathy for physical pain and experimental pain robustly overlap, these results indicate a specific hyperresponsivity of the pain pathways, with the inferior frontal gyrus likely playing a regulatory role in modulating pain-related processes. Finally, the results underscore the translational application potential of neuroaffective multivariate signatures as neuromarkers for pathological dysregulations in affective and pain-related processes.